2010
DOI: 10.1038/icb.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of T‐cell cytokine production by ICOS–B7H2 interactions at the human fetomaternal interface

Abstract: Although T cells are the most common decidual lymphocyte subset in late pregnancy, little is known about the mechanisms controlling their function. Costimulatory signaling, mediated by inducible costimulator (ICOS)-B7H2 interactions, is a known potent regulator of T-cell activation. We aimed to determine its role in fetomaternal immunity. T cells from matched peripheral blood and term decidua were assessed for ICOS, CD4/CD8, CD45RA/CD45RO and Foxp3 expression and for alterations in cytokine production upon ICO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
(77 reference statements)
3
22
1
Order By: Relevance
“…They are absent on resting naive T cells, but are rapidly induced upon antigen recognition (Freeman et al, 2000). We have previously reported that ICOS was highly expressed on the entire T cell population in human decidua (Nagamatsu et al, 2011). The present study confirmed that PD-1 was also present in the majority of decidual T cells, a finding previously reported in a detailed description of decidual PD-1 expression patterns by another group (Taglauer et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They are absent on resting naive T cells, but are rapidly induced upon antigen recognition (Freeman et al, 2000). We have previously reported that ICOS was highly expressed on the entire T cell population in human decidua (Nagamatsu et al, 2011). The present study confirmed that PD-1 was also present in the majority of decidual T cells, a finding previously reported in a detailed description of decidual PD-1 expression patterns by another group (Taglauer et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that decidual stromal cells constitutively express B7-H1 and B7-DC, and that interactions between B7-H1 and B7-DC with their ligands are likely involved in the suppression of excessive T cell activation in the decidua (Nagamatsu et al, 2009). Enhanced expression of inducible costimulator (ICOS), a receptor for B7-H2 (Nagamatsu et al, 2011) and PD-1 (Taglauer et al, 2008) has been confirmed by us and others on a majority of the T cells residing in the decidua. Taken together, these findings imply that B7 costimulatory pathways may be critical in the fine tuning of T cell activity at the feto-maternal interface.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, newly diagnosed type 1 diabetic children had a defect in the induction of FoxP3 and ICOS expression [20]. Furthermore, a substantial expression of ICOS on T regs and decidual T cells was recognized to be crucial for preserving the immune homeostasis at the feto-maternal interface [21]. Of note, the induction of T cell anergy and the suppressive capacity of CD4…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the upregulation of PDCD1 on the CD4 þ T cells in OVA-bred OT-II mice suggests that this molecule may be important in inhibiting fetus-specific maternal CD4 þ T cells that may subsequently encounter CD274-expressing trophoblast cells at the maternalfetal interface and/or CD274-expressing maternal APCs. Although our previous work demonstrates a noncritical role for PDCD1/CD274 interactions in murine pregnancy [39,40]; in experiments using human cells, expression of the ICOS and PDCD1 ligands, ICOSL and CD274, respectively, by trophoblasts and macrophages at the maternal-fetal interface suggest that these receptors function in cytokine modulation during pregnancy [39,[41][42][43][44]. Alternatively, increased expression of PDCD1 may be important in converting CD4 þ T cells into Tregs as has been suggested by others [32,33].…”
Section: Perchellet Et Almentioning
confidence: 84%